2015
DOI: 10.1007/s10439-015-1340-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Head Rotation on the Geometry and Hemodynamics of Healthy Vertebral Arteries

Abstract: The geometric and hemodynamic characteristics of the left and right vertebral arteries (LVA, RVA) of six healthy volunteers were investigated for the supine (S) and the prone position (P) a common sleeping posture with head rotation. MRI images were used to reconstruct the subject specific three-dimensional solid models of the LVA and RVA from the level of the carotid bifurcation to the vertebrobasilar junction (VJ). Geometric parameters such as cross sectional area ratio, curvature, tortuosity and branch angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Previous studies suggest that neck movement can significantly alter vascular morphology in a patient specific fashion. 4 , 5 It is therefore possible that the morphology of an AVF changes when a patient moves or bends their arm. Finally, future work should development both bench-top and in-vivo pre-clinical experiments, in order to validate the computational results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that neck movement can significantly alter vascular morphology in a patient specific fashion. 4 , 5 It is therefore possible that the morphology of an AVF changes when a patient moves or bends their arm. Finally, future work should development both bench-top and in-vivo pre-clinical experiments, in order to validate the computational results.…”
Section: Discussionmentioning
confidence: 99%
“…The image‐based computational modelling methodology employed in the present work, from MR images to CFD simulations allows estimating hemodynamic parameters based on wall shear stress (WSS) metrics, which have been found to be important in the development of thrombosis arising from IH . The accuracy of CFD predictions was investigated by Steinman et al and concluded that the pressure drop was reasonably well predicted …”
Section: Methodsmentioning
confidence: 99%
“…More specifically, Glor et al have first reported that head rotation may cause geometric changes to the right carotid bifurcation with leftward rotation of the head. 11 Then, other researchers cited alterations due to posture changes to the popliteal artery, 12 vertebral arteries, 13 and right and left carotid bifurcation. 14 The objective of this study was therefore to present a methodology to calculate geometric and hemodynamic parameters in healthy arm vessels, and to find their range of variation in two investigated positions.…”
mentioning
confidence: 99%
“…Extensive use of MRI for the generation of geometries for computational modelling and image-based computational fluid dynamics (CFD) can be found in biomedical engineering area, and the generation of geometries from MR images is well established. 7 , 8 , 28 A brief overview of the progress achieved in the field of image-based CFD studies was done by Steinman and Taylor 79 , 85 with applications in research assessing WSS-based metrics. 78 …”
Section: Mrimentioning
confidence: 99%